Assessment of genetically modified maize DP4114 × MON 810 × MIR604 × NK603 and subcombinations, for food and feed uses, under Regulation (EC) No 1829/2003 (application EFSA‐GMO‐NL‐2018‐150). (7th March 2022) - ,; Mullins, Ewen; Bresson, Jean‐Louis; Dalmay, Tamas; Dewhurst, Ian Crawford; Epstein, Michelle M; Firbank, Leslie George; Guerche, Philippe; Hejatko, Jan; Naegeli, Hanspeter; Moreno, Francisco Javier; Nogué, Fabien; et al.
Abstract: Maize DP4114 × MON 810 × MIR604 × NK603 (four‐event stack maize) was produced by conventional crossing to combine four single events: DP4114, MON 810, MIR604 and NK603. The GMO Panel previously assessed the four single maize events and one of the subcombinations and did not identify safety concerns. No new data on the single maize events or the assessed subcombination were identified that could lead to modification of the original conclusions on their safety. The molecular characterisation, comparative analysis (agronomic, phenotypic and compositional characteristics) and the outcome of the toxicological, allergenicity and nutritional assessment indicate that the combination of the single maize events and of the newly expressed proteins in the four‐event stack maize does not give rise to food and feed safety and nutritional concerns. The GMO Panel concludes that the four‐event stack maize, is as safe as the comparator and the selected non‐GM reference varieties. In the case of accidental release of viable grains of the four‐event stack maize into the environment, this would not raise environmental safety concerns. The GMO Panel assessed the likelihood of interactions among the single events in nine of the maize subcombinations not previously assessed and concludes that these are expected to be as safe as the single events, the previously assessed subcombination and the four‐event stack maize. Post‐market monitoring of food/feed is not considered necessary. The post‐market environmental monitoring plan and reporting intervals are in line with the intended uses of the four‐event stack maize. The GMO Panel concludes that the four‐event stack maize and its subcombinations are as safe as the non‐GM comparator and the selected non‐GM reference varieties with respect to potential effects on human and animal health and the environment.